TOLAK UKUR KINERJA TANGGUL BERDASARKAN PENILAIAN KEANDALAN, PENILAIAN PERMUKAAN TANGGUL DAN STABILITAS TANGGUL (Studi Kasus: Ruas Jurug Mojo, Surakata) - Hermawan, Chitra; Suprapto, Mamok; As’ad, Sholihin (Jurnal Teknik Sipil, 2014)
ABSTRACTÂ Flood is known as a disaster that usually comes suddenly, and therefore, people are not prepared. As a result, it causes a dead loss, both human and material. In order to anticipate flood, some dikes have been built.Bengawan Solo dike has changed through time. Damages along the dike have been identified and followed-up by conducting some improvements to make it function well. However, since the repairs are carried out based on the occurrence of landslide or burst, there are many portions of the dike that are damaged but receive no rehabilitation. In fact, in some portions of the dike crossing densely populated settlements, there are many buildings cutting through the outside part of the dike base. Furthermore, portions of the dike in that area have been transformed to street with uncontrolled load. For example, it is found that some vehicles loading construction materials passing on the dike. But, in fact, this sort of loading has not been predicted in the planning. Hence, it is important to foreknow the benchmark of dike performance to assess the performance of dike before landslide or burst occurring.This research was conducted to the Jurug-Mojo portion of Bengawan Solo dike. It is 1.317 m long and is divided into 13 portions, each of which is 100 m long. The parameters applied in this research were cross-section, dike elevation and data about land, while the variables were debit, gravity acceleration, water surface elevation, soil pore index, shearing force, specific weight, and friction angle. There were 3 (three) methods proposed to assess the benchmark of the dike performance, including reliability assessment, dike surface assessment (PCI Mmethod) and dike stability assessment (Bishop Mmethod).The findings of the research are as follows. The maximum debit that can be embanked by the dike is 1,489 m3/s; the reliability index is 0.675; the PCI index is 59.4 (good); the dike stability index before overtopping is 2.771 (stable); the dike stability index when overtopping is 1.075 (unstable), the water stability index when lowering 1 m is 1.775 (stable).Â Keywords: dike, reliability index, stability, PCI (Pavement Condition Index)Â